Assisted reproductive technology outcomes in women with a chronic viral disease. (1st June 2021) - Bourdon, Mathilde; Garnier, Alicia; Maignien, Chloé; Marcellin, Louis; Dulioust, Emmanuel; Sogni, Philippe; Launay, Odile; Cheriet, Khaled Pocate; Patrat, Catherine; Chapron, Charles; Santulli, Pietro
Abstract : Objective: The aim of this study was to evaluate the cumulative live birth rate in women undergoing in-vitro fertilization/intracytoplasmic-sperm-injection (IVF/ICSI) according to the type of chronic viral infection [HIV, hepatitis-B virus (HBV) and hepatitis-C virus (HCV)]. Design: A cohort study. Setting: A tertiary-care university hospital. Participants: Women with a chronic viral illness HIV, HBV or HCV- were followed until four IVF/ICSI cycles had been completed, until delivery or until discontinuation of the treatment before the completion of four cycles. Main outcome measures: The primary outcome was the cumulative live birth rate after up to four IVF/ICSI cycles. Results: A total of 235 women were allocated to the HIV-infected group ( n = 101), the HBV-infected group ( n = 114) and the HCV-infected group ( n = 20). The cumulative live birth rate after four cycles was significantly lower in the HIV-infected women than in those with HBV [39.1%, 95% confidence interval (95% CI): 17.7–60.9 versus 52.8%, 95% CI: 41.6–65.5, respectively; P = 0.004]. Regarding the obstetrical outcomes, the mean birth weight was lower in the HIV-infected women than in those with HBV or HCV. Multivariate analysis indicated that the age, the anti-Müllerian hormone and the number of cycles performed were significantly associated with the chances of a live birth. Conclusion: HIV-infected women had lower cumulative live birth rate than women with chronic hepatitis, and this was due to less favourable ovarian reserve parameters. These findings underscore the need to better inform practitioners and patients regarding fertility issues and the importance of early fertility assessment. However, larger studies are necessary to gain more in-depth knowledge of the direct impact of HIV on live birth rates. Abstract : Supplemental Digital Content is available in the text